Delivery of internet-based cognitive behavioral therapy combined with human-delivered telepsychology in tinnitus sufferers through a chatbot-based mobile app - Bardy, Fabrice; Jacquemin, Laure; Wong, Cara L.; Maslin, Michael R. D.; Purdy, Suzanne C.; Thai-Van, Hung (Frontiers in Audiology and Otology, 2024)
Background: While there is no cure for tinnitus, research has shown that cognitive behavioural therapy (CBT) is effective in managing clinical sequelae. Although traditional CBT is labour-intensive and costly, new online consultations may improve accessibility. Moreover, there is promise in an engaging conversational agent, or a "chatbot", delivering CBT in a conversation-like manner and allowing users to work through complex situations with the guidance of a virtual coach. Currently, there is little research examining a possible hybrid model using iCBT and tele consultation with a psychologist.A randomized, 2 parallel-group trial was conducted to compare the clinical effectiveness of (1) iCBT delivered through a chatbot mobile app (i.e., Tinnibot only group) (2) Tinnibot combined with telepsychology (i.e., hybrid-intervention group). A total of 30 eligible adults with tinnitus were included. After an 8-week intervention period, participants were followed up for 2 months. The primary outcome measure, the Tinnitus Functional Index (TFI), and the secondary outcome measures, Hyperacusis Questionnaire (HQ), Generalized Anxiety Disorder 7-item (GAD-7), and Patient Health Questionnaire (PHQ-9), were assessed before treatment, post-treatment, and at follow-up.The TFI decreased significantly over time in both groups, with a trend for a larger improvement in the group that received telepsychology. At post-treatment, a clinically significant improvement was observed in 42% of the Tinnibot-only group and 64% of the hybrid-intervention group. At follow-up, this was 64% for both groups. The secondary outcome measures, PHQ-9 and GAD-7 improved significantly over time, but the HQ did not. Discussion: Internet-based delivery of CBT is effective in decreasing tinnitus distress, and levels of anxiety and depression, which is more relevant today than ever in the context of a global pandemic that has challenged the delivery of face-to-face intervention. The addition of telepsychology might be beneficial, but not essential for the effectiveness of treatment. There is a need for further research to determine whether there is any relationship between the characteristics of tinnitus patients and the success of the different modes of delivery of therapy.